Impact of Antimicrobial Dipping Solutions on Postoperative Infection Rates in Patients with Diabetes Undergoing Primary Insertion of a Coloplast Titan Inflatable Penile Prosthesis. Issue 10 (15th August 2020) - Towe, Maxwell; Huynh, Linda M.; Osman, Mohamad M.; El-Khatib, Farouk M.; Andrianne, Robert; Barton, Gregory; Broderick, Gregory; Burnett, Arthur L.; Campbell, Jeffrey D.; Clavell-Hernandez, Jonathan; Connor, Jessica; Gross, Martin; et al.
Abstract: Background: Modern-day penile prostheses use infection retardant coating to decrease rates of postoperative infection, subsequently reducing explantation and revision rates as well. The Coloplast Titan models are dipped into antimicrobial solutions right before implantation, and the components used for dipping can be tailored toward the patient. Aim: To compare infection, explantation, and revision rates among different dipping solutions used before implantation for patients with diabetes receiving a Coloplast Titan implant. Methods: We systematically reviewed 932 patients with diabetes receiving a primary penile implant across 18 different centers from the period April 2003 to August 2018. Of those patients, 473 received a Coloplast device, whereas 459 received an AMS device. Data regarding the type of antimicrobial solution used before implantation were recorded for 468 patients receiving a Coloplast Titan, including whether or not they suffered a postoperative infection and if they underwent explantation and/or revision. Outcome rates were compared using Fisher's exact and Pearson's chi-square tests, and logistic regression modeling was performed to account for covariates. Outcomes: The main outcome measures of this study were postoperative infection, explantation, and revision rates. Results: Of the total 932 patients reviewed, 33 suffered a postoperative infection. Of 468 patients receiving Coloplast implants, there was a 3.4% infection rate. The most commonly used antibiotic combination before dipping was vancomycin + gentamicin (59.0%). There was a significantly lower rate of postoperative infection, explantation, and revision when vancomycin + gentamicin was used than those associated with the use of all other dipping solutions ([1.4% vs 6.4%; P = .004], [1.1% vs 8.3%; P < .001], and [2.5% vs 12.5; P < .001], respectively). After adjusting for age, body mass index, preoperative blood glucose level, and hemoglobin A1c, the use of other dips was an independent predictor of postoperative infection (odds ratio: 0.191; P = .049). The inclusion of rifampin in the dipping solution trended toward being a significant risk factor for infection ( P = .057). Including antifungals in the dipping solution did not affect infection ( P = .414), explantation ( P = .421), or revision ( P = .328) rates. Clinical Implications: Vancomycin + gentamicin was the most efficacious combination of antibiotics used for dipping in terms of preventing postoperative infection and subsequent explantation and revision. Strengths and Limitations: Data were sampled across multiple institutions providing a large sample that may be more representative of the population of interest. A key limitation of the study was its retrospective nature, which prevented us from controlling certain variables. Conclusion: The use of rifampin did not provide the same type of protection, possibly representing a shift in resistance patterns of common bacteria responsible for device infection.